Russia, China and the Arctic : cooperation or looming rivalry? - Cheang, Chris (2020)
Russia needs Chinese capital to develop its Arctic region. Yet, Russia remains suspicious and fearful of Chinese ambitions in the Arctic. The arrest of a Russian scientist dealing with Arctic affairs in mid-June 2020, allegedly spying for China, reflects these sentiments.